1993
DOI: 10.3109/01612849309006900
|View full text |Cite
|
Sign up to set email alerts
|

Hard T: the Stressful Nature of Incarceration for Women

Abstract: This descriptive, correlational study explored the stressful life event of incarceration for women prisoners and examined its relationship to selected health outcomes. Interviews with 55 women during their first week of incarceration and after 6 months in prison provided the data for analysis. Specific stresses of incarceration identified by the women included separation from families, worry about their children, and loss of control of their own lives. Psychological stress at time of incarceration was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 8 publications
5
93
0
5
Order By: Relevance
“…This study revealed that upon incarceration in a Federal facility, 44% of the women were obese, however after six months the percentage of obese inmates increased to 57%. Moreover, 17% of the women admitted within normal weight range were obese at the end of the study (Fogel, 1993). These studies indicated that short-term incarceration, whether by increasing stress or altering diet, was followed by weight gain.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This study revealed that upon incarceration in a Federal facility, 44% of the women were obese, however after six months the percentage of obese inmates increased to 57%. Moreover, 17% of the women admitted within normal weight range were obese at the end of the study (Fogel, 1993). These studies indicated that short-term incarceration, whether by increasing stress or altering diet, was followed by weight gain.…”
mentioning
confidence: 88%
“…Weight gain during incarceration was also addressed in a study by Fogel (1993), that examined stress and its long-term outcomes related to clinical depression, physical symptoms and weight gain. This study revealed that upon incarceration in a Federal facility, 44% of the women were obese, however after six months the percentage of obese inmates increased to 57%.…”
mentioning
confidence: 99%
“…In addition to the stresses of incarceration, (Fogel, 1993) incarcerated women are more likely to have experienced past stressful life events such as violence and economic deprivation. Further, the population of incarcerated women includes a disproportionate number of racial and ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Although no studies have yet examined the relationship with reproductive function, stress during incarceration has been shown to be associated with depression, weight gain, and number of physical symptoms reported. (Fogel, 1993) We hypothesize that menstrual dysfunction is highly prevalent among incarcerated women in Rhode Island. This study examines the association between menstrual irregularity and amenorrhea and stressful life experiences in a population of newly incarcerated women.…”
Section: Introductionmentioning
confidence: 99%
“…Fogel (1993) verificou que, na primeira semana de prisão, metade das internas relatou pânico e medo, especialmente de serem molestadas sexualmente e de sofrerem violência física. Mulheres que ficaram detidas na cadeia antes de irem à prisão ouviram histórias terríveis sobre a vida ali, contribuindo para aumentar o medo que estavam sentindo.…”
Section: O Momento Da Admissão O Momento Da Admissão O Momento Da Admunclassified